Cellulose NANOFIBER‐polyethylene nanocomposites modified by polyvinyl alcohol. Issue 6 (24th October 2015) - Kiziltas, Alper; Nazari, Behzad; Kiziltas, Esra Erbas; Gardner, Douglas J. S.; Han, Yousoo; Rushing, Todd S.
ABSTRACT: The uniform dispersion of cellulose nanofibers (CNFs) in non‐polar polymer matrices is a primary problem to overcome in creating novel nanocomposites from these materials. The aim of this study was to produce CNF‐polyethylene (PE) nanocomposites by melt compounding followed by injection molding to investigate the possibility of using polyvinyl alcohol (PVA) to improve the dispersion of CNF in the PE matrix. The tensile strength of CNF‐ filled composites was 17.4 MPa with the addition of 5 wt % CNF–PVA, which was 25% higher than the strength of neat PE. The tensile modulus of elasticity increased by 40% with 5% CNF–PVA addition. Flexural properties also significantly increased with increased CNF loading. Shear viscosity increased with increasing CNF content. The elastic moduli of the PE/CNF composites from rheological measurements were greater than those of the neat PE matrix because of the intrinsic rigidity of CNF. Melt creep compliance decreased by about 13% and 45% for the composites with 5 wt % CNF and 10 wt % CNF, respectively. It is expected that the PVA carrier system can contribute to the development of a process methodology to effectively disperse CNFs containing water in a polymer matrix. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 42933. Abstract :